A homology independent sequence replacement strategy in human cells using a CRISPR nuclease. Issue 1 (27th January 2021) - Danner, Eric; Lebedin, Mikhail; de la Rosa, Kathrin; Kühn, Ralf
Abstract : Abstract : Precision genomic alterations largely rely on homology directed repair (HDR), but targeting without homology using the non-homologous end-joining (NHEJ) pathway has gained attention as a promising alternative. Previous studies demonstrated precise insertions formed by the ligation of donor DNA into a targeted genomic double-strand break in both dividing and non-dividing cells. Here, we demonstrate the use of NHEJ repair to replace genomic segments with donor sequences; we name this method 'Replace' editing (R ational e nd-joining p rotocol del ivering a targeted sequenc e e xchange). Using CRISPR/Cas9, we create two genomic breaks and ligate a donor sequence in-between. This exchange of a genomic for a donor sequence uses neither microhomology nor homology arms. We target four loci in cell lines and show successful exchange of exons in 16–54% of human cells. Using linear amplification methods and deep sequencing, we quantify the diversity of outcomes following Replace editing and profile the ligated interfaces. The ability to replace exons or other genomic sequences in cells not efficiently modified by HDR holds promise for both basic research and medicine.